Control attitudes toward drug use as a function of paternalistic and moralistic principles - Stylianou, Stelios (My University, 2002)
Perceptions of crime seriousness have been studied since the 1960s. Characteristics of acts affecting these perceptions have been identified, and the degree of agreement in seriousness judgments has been examined for a variety of behaviors. The present study extends this inquiry by investigating how perceptions of self-harm and perceptions of immorality shape attitudes toward the control of drug use. These attitudes and perceptions were measured for six widely known drugs - alcohol, cigarettes, cocaine, heroin, LSD, and marijuana - using an electronic mail survey of university students. Univariate analysis shows dissensus rather than consensus in attitudes and perceptions and that, with the exception of marijuana, control attitudes toward drug use reflect the existing legal code. Multivariate analysis shows that perceptions of self-harm and perceptions of immorality are moderately to highly correlated and that control attitudes are strongly affected by perceptions of self-harm and perceptions of immorality.
Keywords: Offense; Penalty; Punitive attitudes